Pendampingan Proses Pengelolaan Sayuran Hortikultura di Desa Gundik Kecamatan Slahung Kabupaten Ponorogo - Muhtarotin Nashirotil Mu’mini; Ahmad Kirom (Institut Agama Islam Sunan Giri Ponorogo, 2023)
Horticulture is a science that studies the cultivation of vegetables, fruits, flowers and ornamental plants. Horticulture is one of the sub-sectors in the agricultural sector that has the potential to be developed because it has a fairly high economic value. Vegetables play an important role in human life, the need for vegetables for the community continues to increase along with population growth while land area is decreasing due to rapid development. Vegetables have various types, besides that vegetables are edible parts of plants. Vegetables are the main food ingredient in our daily lives, apart from being a source of protein and carbohydrates. This study aims to determine the process of managing horticultural vegetables from land preparation, nursery and planting, maintenance, fertilization, irrigation, pests and diseases, harvesting, marketing and income. From this business, respondents can improve the welfare of their families, with daily income of IDR 50,000-IDR 100,000.